Intermittent theta-burst stimulation with physical exercise improves poststroke motor function: A systemic review and meta-analysis - Gao, Bixi; Wang, Yunjiang; Zhang, Dingding; Wang, Zongqi; Wang, Zhong (Frontiers in Neurology, 2022)
Background Intermittent theta-burst stimulation (iTBS) is an optimized rTMS modality that could modulate the excitability of neural structures. Several studies have been conducted to investigate the efficacy of iTBS in improving the motor function of stroke patients. However, the specific role of iTBS in motor function recovery after stroke is unclear. Hence, in our study, we performed a meta-analysis to investigate the efficacy of iTBS for the motor function improvement of stroke patients. Methods MEDLINE, Embase, and Cochrane Library were searched until May 2022 for randomized controlled trials (RCTs). Results Thirteen RCTs with 334 patients were finally included in our study. The primary endpoints were the Fugl-Meyer assessment scale (FMA) and Motor Assessment Scale (MAS) change from baseline. We found that iTBS led to a significant reduction in FMA score (P = 0.002) but not in MAS score (P = 0.24) compared with the sham group. Moreover, standard 600-pulse stimulation showed a better effect on motor function improvement than the sham group (P = 0.004), however, 1200-pulse iTBS showed no effect on motor function improvement after stroke (P = 0.23). The effect of iTBS for improving motor function only exists in chronic stroke patients (P = 0.02) but not in subacute patients (P = 0.27). Conclusion This study supports that iTBS has good efficacy for improving motor function in stroke patients. Therefore, standard 600-pulse stimulation iTBS therapy is proper management and treatment for chronic stroke.